Resistência de genótipos de algodoeiro (Gossypium hirsutum L.) a Alabama argillacea (Hübner) (Lepidoptera: Noctuidae) - Dos Santos, Terezinha M. [UNESP]; Boiça Jr., Arlindo L. [UNESP] (My University, 2001)
Eleven cotton genotypes were evaluated for resistance to A. argillacea, considering biological aspects of young and adult phases of this insect. The trials were conducted in climatic chambers at 25±1°C under relative humidity of 70±10% and photophase of 12h. The first instar was significantly larger when A. argillacea fed on CNPA 94/139 and CNPA Precoce 1 genotypes. During the second instar, the cotton leafworm fed CNPA 94/139 genotype presented significantly shorter period. The variation interval for the third and fourth instars duration was, respectively, 1.8 to 2.1 and 1.9 to 2.2 days. The cotton leafworm fed CNPA Precoce 2 presented fifth instar duration of 4.9 days. The leafworms average weight at 5 days of age was lower when fed CNPA Precoce 1 genotype. The pre-pupal and pupal periods ranged from 1.0 to 1.9 and 7.8 to 8.7 days, respectively. The interval variation for the larval phase was 13.1 to 14.7 days. CNPA Precoce 1, CNPA Precoce 2, CNPA 9211-18 and CNPA 9211-21 genotypes promoted significantly higher duration larva-adult period. During the larval and larva to adult periods, the leafworms fed CNPA 9211-41 and CNPA 9211-31 genotypes leaves presented lower survival rates, 64.2 and 60.7; 62.1 and 58.6% respectively. A. argillacea females originated from leafworms fed CNPA Precoce 1 genotype showed shorter oviposition period and lower number of eggs laid. It was concluded that CNPA 9211-31, CNPA Precoce 1, CNPA Precoce 2 and CNPA 9211-41 genotypes showed antibiosis and/or feeding nonpreference resistance, while GL2 GL3 and CNPA 9211-29 were susceptible to cotton leafworm.
Resistance of cotton genotypes (Gossypium hirsutum L.) to Alabama argillacea (Hübner) (Lepidoptera: Noctuidae)
Keywords: Biology; Cotton leafworm; Host plant resistance; Insecta